The forget-me-not child - Bennett, Anne (London, HarperCollins Publishers, 2017)
A story of struggle and hardship and one girl's battle for survival from the best-selling author of If You Were the Only Girl and Another Man's Child. Angela McCluskey comes to Birmingham from Ireland with her family as a young girl to escape poverty at the turn of the 20th Century, but bad fortune dogs the family as the years pass. Angela marries her childhood sweetheart but tragedy is heaped upon misery when he is called up in the Great War and dies at the Somme. She gives birth to a young daughter called Constance who she must rear on her own, but the worst is yet to come when Angela is raped by drunken soldier on leave. Pregnant and destitute and already with one mouth to feed that she can ill afford, there is nowhere left to turn. What destiny awaits Angela and her unborn child? Caught between the devil and the deep blue sea, will Angela forever be punished for the choices that she makes?
Keywords: Birmingham (England).-- Social life and customs.-- Fiction; Mothers and daughters.-- Fiction; Rape victims.-- Fiction; Single mothers.-- Fiction; Widows.-- Fiction